Tanggung Jawab Penyewa dalam Perjanjian Sewa-Menyewa Kendaraan Bermotor (Mobil) di Desa Tibubeneng Canggu - Ni Made Nindya Maheswari; Anak Agung Sagung Laksmi Dewi; I Putu Gede Seputra (Jurnal Konstruksi Hukum, 2021)
This study aims to determine the tenants' responsibilities in case of default in the motor vehicle rental agreement (car) in the village of Tibubeneng Canggu and to find out the settlement of default by the rent car against the tenants in the village of Tibubeneng Canggu. The research method used is empirical legal research with a sociology of law approach. This study uses primary data derived from observations and interviews obtained from 3 rent car owners in the village of Tibubeneng Canggu. Data collection used interview techniques, observation and inventory using qualitative analysis techniques. The results of the analysis show that the tenant's responsibility in the event of default in the motor vehicle (car) rental agreement in the village of Tibubeneng Canggu in terms of overtime is in the form of compensation by paying a fine in accordance with the agreed agreement. The settlement of default carried out by the rent car against the tenant in the village of Tibubeneng Canggu is an alternative dispute resolution through negotiation between the tenant and the rent car party. In order to reduce the occurrence of defaults in the case of overtime car returns, Rent Car pays attention to the clauses of the agreement with the tenant, especially in terms of overtime, so that it is made in a written agreement, and implements a full payment payment system in advance so as not to suffer losses. In addition, the tenant is expected to read and comply more with the contents of the agreement so that there are no negligence that can cause harm to the Rent Car